2022
DOI: 10.5694/mja2.51638
|View full text |Cite
|
Sign up to set email alerts
|

Transforming health settings to address gender‐based violence in Australia

Abstract: ender-based violence includes physical, psychological, sexual or economic behaviour causing harm for reasons associated with people's gender. 1 A violation of human rights, women are disproportionately affected by gender-based violence, 2 with Indigenous women and girls facing particularly high risk. 3 Globally, the gender-based violence types most widely studied are domestic and sexual violence, with 35% of women worldwide experiencing either or both during their lifetime. 2 Australian national studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Despite both study sites being selected for serving families experiencing disadvantage, the study found different patterns of identification of, and response to, adversity that may be explained by the sociodemographic compositions of each community, service infrastructure and workforce composition. The influence of service context detected in this study also highlights the need to incorporate contextual factors into the implementation of broad programs in health settings (e.g., primary care, antenatal care) around detection and response to family violence ( 42 ) and financial need ( 43 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Despite both study sites being selected for serving families experiencing disadvantage, the study found different patterns of identification of, and response to, adversity that may be explained by the sociodemographic compositions of each community, service infrastructure and workforce composition. The influence of service context detected in this study also highlights the need to incorporate contextual factors into the implementation of broad programs in health settings (e.g., primary care, antenatal care) around detection and response to family violence ( 42 ) and financial need ( 43 ).…”
Section: Discussionmentioning
confidence: 86%
“…. primary care, antenatal care) around detection and response to family violence (42) and financial need (43).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…For example, a study using the disease burden method in Australia found that among women aged 18 to 44 years, GBV is associated with 7% of the disease burden. This violence is more important than the factors usually considered, such as high blood pressure (hypertension), smoking, and being overweight (41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies show that IPV is the most common cause of injury for female victims [ 2 , 10 ]. This has led to IPV research in healthcare settings and online focusing on interventions for women survivors [ 11 , 12 ]. Yet, current policy and practice suggest that efforts to end IPV must also target men potentially using IPV in their intimate relationships with female, male and non-binary partners [ 13 ].…”
Section: Introductionmentioning
confidence: 99%